Spinoza: Journal of an Emendation - Martinon, Jean-Paul (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2026)
For the last 350 years, nearly all writing devoted to Spinoza is exegetic, providing endless interpretations of his many propositions, axioms, definitions, and scholia. When reflecting on this enormous corpus, the following question immediately springs to mind: instead of adding one more interpretation to Spinoza's scholarship, is it possible to undertake the emending project that he proposes in his Treatise on the Emendation of the Intellect and the Ethics? Emendation does not mean altering for the better, but simply choosing a better perspective. Can such a change of perspective be actually achieved? This book attempts to carefully follow and live out Spinoza's emendation project today.